Research on the Digital Design of Gear Transmission Scheme - Wei Shan; Lianji Wang; Yali Ma; Guangjian Wang (Jixie chuandong)
The knowledge units of gear transmission scheme digital design are established，and the motion，dynamic and structural attributes of the knowledge units are extracted. From the state space theory of mechanical motion scheme design，the motion and dynamic attributes of the knowledge units are transformed into feature vectors，so that the solution of gear transmission scheme is converted into a matrix calculation. The relationship between dynamic attributes of knowledge units and 3D parametric model is established to realize the visualization of transmission scheme. The knowledge unit database of the gear transmission scheme is established and transformed into the corresponding data structure. The solution of hybrid combination schemes of knowledge units is implemented by considering the series-parallel combination of knowledge units. The gear transmission scheme design module，which is developed by VS，is used to output the three-dimensional model of the gear transmission scheme meeting the user's requirements and the relevant details of the scheme.